Financial development and economic growth: evidence from panel data - Nurzamira, Ahmat (2016)
This study examines the relationship between financial development and growth in ASEAN by using panel ordinary least squares and causality analysis. In this study gross domestic products (GDP) is used to represent growth and the ratio of money supply to GDP represents financial development. There are also other variables such as exchange rates, foreign direct investment (FDI) and total population are being used as independent variables. Panel Ordinary Least Squares (POLS) had been used to investigate the relationship between growth and financial development and we found that all the independent variables in this study generally have significant relationship with growth. In addition, this study conducted Granger causality test and the test results confirmed that a unidirectional causal relationship exists between foreign direct investment and population has causal impact which run from foreign direct investment to population. There is also a unidirectional causal relationship can be found to exist running from the exchange rate to financial development. Finally in conclusion, in order to improve growth of the country, government as a policy maker play an important role to encourage investment by providing or upgrading infrastructures and facilities in order to generate more opportunities furthermore to create competition and productivity in the economy.